2018
DOI: 10.3389/fpsyg.2018.02199
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Distress of Patients at End-of-Life and Their Caregivers: Interrelation and Predictors

Abstract: Background: Patients at the end of life and their families experience a strong emotional impact. The well-being of these patients and that of their family caregiver are related.Aim: To study the variables related with the emotional well-being of patients with and without cognitive impairment at the end of life and that of their primary family caregivers.Design: Cross- sectional study.Participants: Data was collected from 202 patients at the end of life with different diagnosis (COPD, cancer, and frail elderly)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 57 publications
1
18
0
6
Order By: Relevance
“…Based on the linear regression analysis, both the family caregiver's emotional distress and his/her burden predict the distress of the patient, in conjunction with the patient's functional independence and the time living with the disease. The interrelation between the family caregiver's emotional distress and the emotional distress of the end-of-life patient as a dyad goes in line with previous literature [ 22 , 23 ]. In this study, this interrelation can be observed via the regression analysis as well as with the QCA analysis, and it highlights once more the importance of attending to the emotional needs of patients and their families in the palliative settings, considering the patient and their main family caregiver as a system.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Based on the linear regression analysis, both the family caregiver's emotional distress and his/her burden predict the distress of the patient, in conjunction with the patient's functional independence and the time living with the disease. The interrelation between the family caregiver's emotional distress and the emotional distress of the end-of-life patient as a dyad goes in line with previous literature [ 22 , 23 ]. In this study, this interrelation can be observed via the regression analysis as well as with the QCA analysis, and it highlights once more the importance of attending to the emotional needs of patients and their families in the palliative settings, considering the patient and their main family caregiver as a system.…”
Section: Discussionsupporting
confidence: 86%
“…Several pathways predict the variance observed in the emotional distress of family caregivers of end-of-life patients with COPD. Based on the linear regression analysis and the QCA, the medical variables of the patient, such as time since diagnosis, number of hospital admissions, comorbidity and functional dependence play an essential role in the emotional distress of the family, as does the emotional distress of the patient [ 22 , 23 ]. The relevance of family caregiver burden is fundamental in preventing their emotional distress, so future studies focused on designing intervention programs in this regard should consider the importance of including elements to reduce the caregiver burden [ 13 , 17 , 19 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erst als weiterer Schwerpunkt werden von den Angehörigen die eigenen emotionalen Bedürfnisse angegeben [25], deren Ausgangspunkte Erschöpfung, Schuldgefühle, Ärger, Traurigkeit, Ängste, Einsamkeit, Hilflosigkeit oder Ungewissheit darstellen [20] und die verstärkt in der Sterbephase und nach dem Tod des Patienten auftreten [21]. Pflegende Angehörige wollen zudem vom Palliativteam in ihrer Rolle als Hilfegebende gesehen und wertgeschätzt [27] und nach ihren Gefühlen und ihrem Befinden gefragt werden [17].…”
Section: Introductionunclassified